Freedom of Information and the Library - Stosic, Milica Cvetkovic (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
The present article examines progress in reorienting libraries towards more effective participation in the freedom of information process. In 1997 the International Federation of Library Associations (IFLA) set up its Freedom of Access to Information and Freedom of Expression (FAIFE) Committee to promote information rights in the context of libraries. In 2008, an IFLA Manifesto on Transparency, Good Governance and Freedom from Corruption was adopted. Learning materials derived from this manifesto were first piloted in Vietnam and India. Further workshops were held in Iceland and Argentina and the success of the whole program has culminated in the Serbian experience.